PROSES BERPIKIR ALJABAR SISWA DALAM MEMECAHKAN PERMASALAHAN MATEMATIKA BERDASARKAN KEMAMPUAN ALJABAR DAN GENDER - Naziroh, Irmu Afin; Suharto, S; Yudianto, Erfan; Hobri, H; Murtikusuma, Randi Pratama (Kadikma, 2018)
Abstract. Algebraic thinking is a process of solving mathematical problems in which uses letters (variables) and perform deeper activity such as problem identifications, represent information symbolically, make mathematic model, as well as interpret and applying mathematic findings. This research was conducted to describe how algebraic thinking process of Junior High School student based on gender and math ability. The subject of research was divided into two of student with high math ability, two student with mid math ability and two student with low math ability in mathematical problem solving of linier equation system of two variable for C5 and C6 problems category where in each category consist of boy and girl. The result shows for C5 and C6 problems, student with high and mid math ability both boys and girls were capable of algebraic thinking in every steps of problem solving. Student with low math ability, the boy was capable of algebraic thinking in every steps of problem solving for C5 and C6 problems. Whereas the girl capable of algebraic thinking in every steps, but for C6 problem category, the girl was only able to perform two algebraic thinking activity in problem solving. Keywords: algebraic thinking, mathematic ability, problem solving